ANALISIS HUKUM EKONOMI SYARIAH TERHADAP AKAD DALAM PROGRAM BPJS KESEHATAN - Saniah, Nur (Islamic Circle, 2021)
In principle, public health insurance is one of the tasks of the state. Indonesia as a large country has regulated social security in the form of health prevention for the community, manifested in the form of the JKN (National Health Insurance) program organized by the Social Security Administering Body (BPJS). Indonesia as a country with a majority Muslim population, of course, does not accept the decision of the government regulation immediately, one of which is whether the contract in the BPJS health program is in accordance with Islamic law?, because Muslims cannot be separated from their religious rules which regulate in all aspects, including health insurance. To answer this problem, research was carried out, using data collection techniques in the form of documentation of everything related to the research title. After the data was collected, it was analyzed by qualitative analysis using descriptive analysis method. The results of the study found that the contract used by the BPJS health program is allowed as long as the meaning is understood by each party (no gharar) and the existence of mutual blessing (an taradhin) is the main requirement in every muamalah contract, so that it does not result in consuming other people's property in a false way. or not contrary to sharia provisions.